The inspection of the granted use of water resources in a basin declared in a critical situation of water scarcity. Case study: case study in the Suaçui River watershed - MG (Research, Society and Development, 2020)
In the framework of the Minas Gerais State Water Resources Policy, was published in 2015, Normative Deliberation No. 49 of March 25, 2015, amended by CERH-MG Normative Deliberation No. 50 of October 9, 2015, which establishes guidelines and general criteria for the definition of Critical Situation of Water Shortage and Restricted State of Use of Surface Water Resources in the hydrographic portions of the State of Minas Gerais. The present work aimed to analyze the effectiveness of such legislation, as a way to ensure the prevention or mitigation of damage from the occurrence of adverse hydrological events such as: preventing or minimizing the effects of drought; prevent or alleviate severe environmental degradation; meeting priority uses; and minimize impacts on multiple uses. From data obtained from the environmental agencies managing water resources, an analysis was performed on the act that declared Critical Situation of Water Shortage and State of Restricted Use in the hydrographic portion upstream of Vila Matias Station, Suaçui River basin, and the actions taken by environmental agencies in order to comply with current legislation. The analysis showed that during the enforcement action on the granted users, it was not possible in any of the uses to measure the flow captured, and consequently to verify if the imposed restrictions of use were taken. However, due to non-compliance with the obligation to install flowmeter and hourmeter equipment, 75% of the supervised uses were assessed and suspended, which contributed to mitigate the effects of drought in the basin.